From simplicity to complexity: A path to innovation in science and art - Joseph L. Goldstein (Proceedings of the National Academy of Sciences, 2025)
Simple reductionist systems can serve as powerful catalysts for unlocking complex innovations in science and art. The evolution from simplicity to complexity is illustrated by the career journeys of the scientist Earl W. Sutherland, who discovered cyclic adenosine 3′-5′-monophosphate (cyclic AMP) and opened the field of cell signaling, and the artist Frank Stella, who pioneered geometrical patterns and shapes in both painting and sculpture. Their work profoundly influenced biomedical science and modern art. How one navigates the journey from simplicity to complexity is a fundamental challenge to scientists and artists who aim to identify fresh ideas that lead to insights with lasting impact.